Follow The Money Approach in The Management of Fishing Criminals by Fisheries PPNS - Zakariya, Rizki (Universitas Negeri Semarang, 2020)
The many cases of Illegal Fishing, threaten the wealth of fisheries and sovereignty of Indonesia. This study aims to explain the urgency of the Follow the Money approach in handling fisheries crime cases by PPNS Fisheries. Then provide concrete recommendations for the Follow the Money implementation in handling fisheries crime cases. This paper is a normative juridical study, which is processed qualitatively. The results of this study indicate the urgency of the Follow the Money approach in handling fisheries crime cases by PPNS Fisheries due to Indonesia's large fishery wealth; the magnitude of the threat of illegal fishing in Indonesia; lack of fisheries crime cases handled by PPNS Fisheries; and the development of the modus operandi of fisheries criminals.